In silico characterization of laccase gene isoforms of edible and medicinal basidiomycetes (Research, Society and Development, 2020)
Laccases are part of the family of ligninolytic enzymes and have played essential roles in several biological filamentous fungi processes, including fruiting body formation and lignin degradation. This study aimed to identify and characterize laccase genes in silico of several basidiomycete strains. The applied guaiacol oxidation test allowed the selection of seven out of 11 strains with ligninase activity, which were used for DNA extraction and amplification of the copper-binding region. A single amplicon of approximately 450 bp, was produced by all selected strains and they were further sequenced. Sequence analysis has suggested the presence of a new subdivision of the laccase genes. Clustering analysis confirmed the existence of two groups: cluster A with six strains and singleton B with U8-11 strain. The structural predictions of the U8-11 protein were dissimilar compared to other proteins described in our study due to the absence of the ALAVIN motif and, therefore, the U8-11 amino acid sequence was separated in a different cluster.